(untitled) (Revista Argentina de Cirugía, 2026)
The adrenal gland is a common site of metastasis but isolated adrenal gland metastases are rare. The true incidence of adrenal involvement secondary to cutaneous melanoma is unknown, but the literature describes autopsy series with an incidence of 36-54%. Currently, the decision-making and management of melanoma metastases takes into account factors such as location of metasis, disease burden, need for adjuvant therapies, and patient’s clinical status. We report the case of a 60-year-old male patient with a diagnosis of melanoma in the right subscapular region with a Breslow thickness of 10 mm and lymph node metastases who underwent tumor resection and axillary lymph node clearance. He received postoperative treatment with pembrolizumab. One year after the initial diagnosis he was diagnosed with an isolated adrenal gland metastasis. The patient underwent laparoscopic adrenalectomy and continued with systemic therapy.